Peter Doherty on zoonotic plagues - Doherty, Peter F. (International Livestock Research Institute, 2016)
Peter Doherty, Nobel Prize Laureate for Physiology or Medicine–1996, and ILRI patron, on zoonotic plagues. Filmed in September 2016.